Effectiveness of create sensitivity model on glycemic control and quality of life among patients with type 2 diabetes - Dini Rudini; Yulia Indah Permata Sari; Putri Irwanti Sari; Yosi Oktarina (Faculty of Nursing Universitas Padjadjaran, 2025)
Background: Type 2 diabetes significantly affects patients' quality of life (QOL). The